Le sentiment amoureux chez les filles et les garçons entre 6 et 11 ans : son implication dans le mode de construction identitaire de genre - Sophie Ruel (Recherches en Éducation)
This article aims to show that young girls’ understanding of love differs from that of boys and will attempt to shed light on the reasons why this is so by citing, in particular, the influence of peer pressure and television shows, from which children draw their values and points of reference and which contribute to representations of love. This study also seeks to evaluate to what extent these differences may influence the development of masculine and feminine identities. Examination of the polymorphous conception of relationships, the influence of peers in the context of childhood romance and the role of sentimental registers in television shows will provide the main axes of investigation in deciphering the construction of gender identity in children.